Computer-Assisted Assembly Language Programming Laboratory - Rodríguez, Santiago; Pedraza, José L.; García, Antonio; Rosales, Francisco; Méndez, Rafael (International journal of electrical engineering & education, 2007)
This paper presents a new approach for managing laboratory work mini-projects that is used in the Computer Architecture Department of the Technical University of Madrid (UPM). The approach is based on a chain of tools (a Delivery Agent; an Automatic Project Evaluator; and a Plagiarism Detection Assistant) that a small number of teachers can use to efficiently manage a course with a large number of students (400 each year). Students use this tool chain to complete the Assembly Language Programming laboratory assignments using an MC88110 simulator built in our department. Jointly, these tools have demonstrated over the last decade what important benefits can be gained from the exploitation of a global laboratory work management system. Some of the benefits may have a continuation in an area of growing importance that we have not yet explored, such as distance learning environments for technical subjects.